Synthesis, characterization and photocatalytic evaluation of visible light activated C-doped TiO 2 nanoparticles - Liu, G.; Han, C.; Pelaez, M.; Zhu, D.; Liao, S.; V. Likodimos; Ioannidis, N; A. G. Kontos; P. Falaras; Dunlop, P.S.M.; Byrne, J.A.; Dionysiou, D.D. (Nanotechnology, 2012)
We have demonstrated heterogeneous photocatalytic degradation of microcystin-LR (MC-LR) by visible light activated carbon doped TiO 2 (C-TiO 2) nanoparticles, synthesized by a modified sol-gel route based on the self-assembly technique exploiting oleic acid as a pore directing agent and carbon source. The C-TiO 2 nanoparticles crystallize in anatase phase despite the low calcination temperature of 350°C and exhibit a highly porous structure that can be optimized by tuning the concentration of the oleic acid surfactant. The carbon modified nanomaterials exhibited enhanced absorption in the broad visible light region together with an apparent red shift in the optical absorption edge by 0.5eV (2.69eV), compared to the 3.18eV of reference anatase TiO 2. Carbon species were identified by x-ray photoelectron spectroscopy analysis through the formation of both Ti-C and C-O bonds, indicative of substitution of carbon for oxygen atoms and the formation of carbonates, respectively. Electron paramagnetic resonance spectroscopy revealed the formation of two carbon related paramagnetic centers in C-TiO 2, whose intensity was markedly enhanced under visible light illumination, pointing to the formation of localized states within the anatase band gap, following carbon doping. The photocatalytic activity of C-TiO 2 nanomaterials was evaluated for the degradation of MC-LR at pH 3.0 under visible light (λ>420nm) irradiation. The doped materials showed a higher MC-LR degradation rate than reference TiO 2, behavior that is attributed to the incorporation of carbon into the titania lattice. © 2012 IOP Publishing Ltd.
cited By 101